Método para análise de desempenho no critério funcionalidade e acessibilidade dos sistemas em madeira para coberturas de edificações segundo a NBR 15.575/2008 - Oliveira, Gabriel Ruiz de (2012)
This study aims to understand traditional building techniques for more sustainable buildings. Its main purpose is to analyze how roof structures made of Wood respond/meet the functionality and accessibility criteria established by the NBR 15.575/2008. Starting from a literature review on the building's performance rating and wood as a construction material, three high standard residential wood roofs designed in Curitiba were analyzed by an evaluation matrix suggested in the research according to the norm's requirements. As results, none of the analyzed projects fulfill the norm's functionality and accessibility performance criteria, though it can be done by a proper design conception elaborated by professionals with technical knowledge. For the conclusion, the NBR 15.575/2008 performance criteria and requirements do not determinates specific solutions, but establish parameters to the technological development of new and efficient ones. This norm still attributes higher responsibilities to the designers, who need to improve their technical knowledge and favor the interaction between professionals to improve the projects compatibilization.